History and lexical and word-formative types of proto-slavic noun suffix -va - Bilousenko, Petro; Sablina, Svitlana (Ukrainian linguistics, 2017)
On the material reconstructed derivates of proto-Slavic era a lexical-derivational taxonomy of feminine nouns with the suffix –VA is carried out. The origin and the typology of derivational suffix-va in such derivatives are established. It is proved that the suffix -VA demonstrates the ability to be combined mostly with verbal and nominal bases. Minor frequency of the creation of proto-Slavic nouns by attaching to the original foundations of the suffix -VA and different types of semantic-derivational specifics of such derivative testify in favor of assumptions about the variant of the semantic-derivational behavior of this formant, and the lack of primary word-formation functions in proto-Slavic era. It is found that the formant -VA had a distinct word-formation potential with the creation of protoSlavic nouns abstract-deverbative. In verbal morphology this particle was sometimes a marker of collectivity in nouns. In proto-Slavic era deadjectival, which are created from noun, are not uniquely identify the primary function of this suffix, since it was formed besubstantial for the representation of names of plants, household utensils, somatisms and collective nouns. Lexical-derivational typology derived from the adjective with suffix -VA is represented by two groups: the names of persons and names of animals. Information about the authors: Petro Bilousenko – Dr Hab, Prof. of the Department of the Ukrainian Language, Zaporizhzhya National University (Ukraine). E-mail: biloysenko@nas.gov.ua Svitlana Sablina – PhD, Associate Prof. of the Department of the Ukrainian Language, Zaporizhzhya National University (Ukraine). E-mail: sablinasv2017@gmail.com __________ References • Bernshtejn S.B. (1974) Ocherk sravnitel’noj grammatiki slavjanskih jazykov. Cheredovanija. Imennye osnovy [Essay on the comparative grammar of the Slavic languages. Alternation. Nominal basis]. Moscow: Nauka, 379 p. (in Russia). • Bilousenko P.I. (2009) Narysy z istoriji ukrajinsjkogho slovotvorennja (sufiks -yna) [Essays on the history of Ukrainian word formation (suffix -ina)]. Zaporizhzhja-Jalta-Kyiv: TOV “LIPS”, 250 p. (in Ukrainian). • Bilousenko P. I. (2013) Istorija ukrajinsjkoji movy. Slovotvir. Ch. 1. Imennyk (prospekt) [The history of the Ukrainian language. Word formation. Part 1. Noun (prospect)]. Zaporizhzhja-Kyiv: ZNU, 82 p. (in Ukrainian). • Mel`nychuk O.S. (ed.) (1966) Vstup do porivnjaljno-istorychnogho vyvchennja slov’jansjkykh mov [Introduction to the comparative historical study of Slavic languages]. Kyiv: Naukova dumka, 586 p. (in Ukrainian). • Jekkert R. (1959) K voprosu o sostave gruppy imen s osnovoj na ŭ praslavjanskom jazyke [The question of the composition of the group name based on the Slavonic language]. Questions of Slavic linguistics. no.4, pp. 100–129 (in Russia). • Maresh V.F. (1961) Slavjankoe vdovica [Slavic widow]. Questions of Slavic linguistics, no. 5, pp.138–148 (in Russia). • Meje A. (1951) Obshheslavjanskij jazik [Slavic language]. Moscow: Izdatel’stvo inostrannoj literatury, 492 p. (in Russia). • Trubachev O.N. (2009) Trudy po jetimologii. Slovo. Istorija. Kul’tura [Works on etymology. Word. Нistory. Culture]. Moscow: Jazyki slavjanskoj kul’tury, vol. 4, 696 p. (in Russia). • Vaillant A. (1974) Grammaire comparée des langues slaves. Tome ІV. La formation des noms. Lyon: IAC, 809 p. • Sławski F. (1974) Zarys słowotworstwa prasłowian’skiego. Słownik prasłowian’ski: In 3 Vols. Wrocław-Warszawa-Krakow-Gdan’sk: Widawnictwo Połskiej Akademii Nauk (in Poland).